Usc/fibred entropy structure and applications. Issue 3 (3rd July 2017) - Burguet, David
ABSTRACT: For a given metrizable space X, we study continuity properties of the entropy as function not only of the measure but also of the dynamical system on X . We introduce the notion of robust tail entropy, which implies upper semicontinuity of the topological entropy but also stability of measures of maximal entropy (when the topological entropy is continuous). This gives, inter alia, simple proofs of results of Misiurewicz and Raith for multimodal interval maps. We also consider fibred entropy structures which allow us to investigate the symbolic extensions of (smooth) skew-product systems.